INTEGRASI KURIKULUM PESANTREN DAN MADRASAH PADA PONDOK PESANTREN MANBA'UL 'ULUM SINDANGMEKAR DUKUPUNTANG CIREBON - Siti Maryam Munjiat (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2017)
ABSTRACT            Turbulence of education in Indonesia has been experienced since a period of Netherland Colonial, both of general or religion. In the earlier Islamic education institute in this case is Pesantren (Islamic Boarding School) representing eldest institute in Indonesia with traditional characteristic have felt direct collision with Netherland Colonial, which according to their doctorine of Pesantren resistance for them. Leaving from this, then there is polarization between Pesantren (Islamic Boarding School) and school as a product of Netherland that born general school triggering dichotomies. But, there any dissimiliar factor that continue the existence of the dichotomies without confusing the value of education and optimal achievement?            The aim of this research to reply and explain about factors of the happening the integration of curriculum. Others also, research intended to lift the spirit of education institute base on religion, that is Pesantren an Madrasah (representing gene from pesantren with systematic curriculum) in integrating both of curriculum both. One all important matter again in this research is eliminate boundary and apart between general science and theology with existence integrate curriculum as have done all his predecessor, that is Pesantren Gontor Ponorogo, Pesantren Darul Arqom Garut, Pesantren al-Amin Madura with different manner and pattern. Existing also in Pesantren manba'ul 'Ulum Cirebon represent object of research that is about the integration.            The integration of curriculum at education institute base on religion (Pesantren and Madrasah) have successful result such as those which reached for by big name of Pesantren Gontor Ponorogo and then followed by other Pesantren and proven from exponent, output from each Pesantren when have acted in society.      Method of this research is used field research-field research that having the character of analytic descriptive that is in order to object the research can be explained and formulated and also analyse the happening integration of curriculum.            The result obtained in this research is the manifestation from integration curriculum Pesantren and Madrasah implemented at Pesantren Manba'ul 'Ulum Sindangmekar Dukupuntang Cirebon is not quit of the general and religion science, epoch demand, study continuation of all Santri (student of Pesantren), legitimating from society and government. All of them represent mutual framed in social-culture.  Keywords: Curriculum Integration, Madrasah, and Pesantren